Morphometric analysis of Chagasia fajardi (Diptera: Culicidae) populations in Brazil - DOS SANTOS SILVA, JÚLIA; CARBAJAL DE LA FUENTE, ANA LAURA; SERRA-FREIRE, NICOLAU MAUÉS; ÉRICO-GUIMARÃES, ANTHONY; SOARES-SARMENTO, JULIANA; ALENCAR, JERONIMO (Revista Colombiana de Entomología, 2012)
The objective of the present study was to evaluate morphological variability in four populations of Chagasia fajardi using classic morphometry. Seven variables of the body were measured in specimens of Ch. fajardi from four biogeographical regions of Brazil, including three populations from the Atlantic Forest biome and one population from the Cerrado biome, were measured. Using analysis of variance (ANOVA), the diagnostic characteristic of the black band on the hindtarsus (Ta-III3) presented strong potential for demonstrating dissimilarity between populations, which were all different from each other. This was followed by the white band on the hindtarsus (Ta-III5) and the wing length (Wl), which showed the presence of two populations similar between themselves, but different from the others. However, multivariate analysis and UPGMA dendograms showed close proximity between populations 2 and 4 and between populations 1 and 3. Morphological variables of Ch. fajardi populations from different regions of Brazil are discussed.